Psychotherapy use in bipolar disorder: Association with functioning and illness severity. (May 2015) - Sylvia, Louisa G; Thase, Michael E; Reilly-Harrington, Noreen A; Salcedo, Stephanie; Brody, Benjamin; Kinrys, Gustavo; Kemp, David; Shelton, Richard C; McElroy, Susan L; Kocsis, James H; Bobo, William V; Kamali, Masoud; et al.
Objective: This study examines characteristics of individuals with bipolar disorder who sought psychotherapy versus those who did not. Methods: Bipolar CHOICE was an 11-site comparative effectiveness study of lithium versus quetiapine in symptomatic outpatients ( N = 482) with bipolar disorder. At baseline, participants' psychotherapy use within the past 3 months, mood, functioning, and overall health were assessed. Logistic regressions were used to test whether psychotherapy users and non-users differed on various demographic and clinical variables at baseline. Mixed-effects regression was used to determine whether psychotherapy groups differed on response to treatment over the 6-month study. Kaplan-Meier plots and log-rank tests were employed to test whether there were any differences in time to recovery (CGI-BP ≤ 2 for at least 8 weeks) between the groups. Results: Thirty one percent of participants reported using psychotherapy services. Psychotherapy users reported greater medication side effect burden than non-users and were more likely to have moderate to high suicide risk and at least one anxiety disorder. Participants not utilizing medications or psychotherapy had greater mania symptom severity, were younger, and less educated than medication only users. Medication only users were more likely to be married than the other participants. Conclusions: These data suggest that a minority of individuals with bipolar disorder attend psychotherapy services, and those that do have greater illness burden.